[Conference report] Sami Prehistory and Early History in the Western Barents Region (SAMIARC) - Larsson, Thomas (Journal of Northern Studies, 2007)
In October 2006 the first meeting of the NordForsk network project Sami Prehistory and Early History in the Western Barents Region (SAMIARC) was held in Rovaniemi, Finland.